Bacterial Pathogens and Symbionts Harboured by Ixodes ricinus Ticks Parasitising Red Squirrels in the United Kingdom - Luu, Lisa (Pathogens, 2021)
Red squirrels (Sciurus vulgaris) are native to most of Eurasia; in much of the United Kingdom, they have been supplanted by the non-native grey squirrel, and are considered an endangered species. Very little is known about the range of tick-borne pathogens to which UK red squirrels are exposed. As part of trap-and-release surveys examining prevalence of Mycobacterium spp. in red squirrel populations on two UK islands, Ixodes ricinus ticks were removed from squirrels and PCR screened for Borrelia spp., intracellular arthropod-borne bacteria and the parasitic wasp Ixodiphagus hookeri. At both sites, the most commonly encountered tick-transmitted bacterium was Borrelia burgdorferi sensu lato (overall minimum prevalence 12.7%), followed by Anaplasma phagocytophilum (overall minimum prevalence 1.6%). Single ticks infected with Spiroplasma were found at both sites, and single ticks infected with Borrelia miyamotoi or an Ehrlichia sp. at one site. Ticks harbouring Wolbachia (overall minimum prevalence 15.2%) were all positive for I. hookeri. Our study shows that UK red squirrels are potentially exposed to a variety of bacterial pathogens via feeding ticks. The effects on the health and survival of this already vulnerable wildlife species are unknown, and further studies are needed to evaluate the threat posed to red squirrels by Borrelia and other tick-borne pathogens.